2012
DOI: 10.1100/2012/217518
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Breath Condensate: A Promising Source for Biomarkers of Lung Disease

Abstract: Exhaled breath condensate (EBC) has been increasingly studied as a noninvasive research method for sampling the alveolar and airway space and is recognized as a promising source of biomarkers of lung diseases. Substances measured in EBC include oxidative stress and inflammatory mediators, such as arachidonic acid derivatives, reactive oxygen/nitrogen species, reduced and oxidized glutathione, and inflammatory cytokines. Although EBC has great potential as a source of biomarkers in many lung diseases, the low c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 67 publications
0
39
0
Order By: Relevance
“…Through PLS-DA 10-times cross-validation tests, we demonstrated that the host breath volatiles were selective and specific predictors of the source of lysate exposure (table 2). There have been efforts to use cytokines as biomarkers of lung disease and injury [1922]. In this study, the cytokine concentrations in BALF were not nuanced enough to distinguish between exposures to P. aeruginosa and S. aureus cell lysates up to 120 h (fig.…”
Section: Discussionmentioning
confidence: 91%
“…Through PLS-DA 10-times cross-validation tests, we demonstrated that the host breath volatiles were selective and specific predictors of the source of lysate exposure (table 2). There have been efforts to use cytokines as biomarkers of lung disease and injury [1922]. In this study, the cytokine concentrations in BALF were not nuanced enough to distinguish between exposures to P. aeruginosa and S. aureus cell lysates up to 120 h (fig.…”
Section: Discussionmentioning
confidence: 91%
“…As biomarkers of pulmonary pathophysiology, we measured exhaled breath condensate (EBC) malondialdehyde (MDA) for oxidative stress;[11] fractional exhaled nitric oxide (FeNO),[12] EBC pH, and EBC nitrite and nitrate (EBCNN) for inflammation;[11] and FEV 1 , FVC, and FEV 1 /FVC ratio for lung function. Measured biomarkers of systemic inflammation and oxidative stress included C-reactive protein (CRP),[13] urinary 8-hydroxy-2’-deoxyguanosine (8-OHdG),[14] and urinary MDA (UMDA).…”
Section: Methodsmentioning
confidence: 99%
“…Due to their size, proteins, including cytokines, are invariably present in low levels close to or under detection limit. Increased levels of reactive oxidative markers and eicosanoid mediators (8--isoprostane and leukotrienes) can be more readily and reproducibly measured [ 132,133 ].…”
Section: Exhaled Breath Condensate (Ebc)mentioning
confidence: 99%